Sistem Pendukung Keputusan Seleksi Penerimaan Beasiswa Bidikmisi Menggunakan Teorema Bayes - Qolbiah Fitri; Muhammad Sya’bani; Asmah; Gusmana, Roman (Journal of Big Data Analytic and Artificial Intelligence, 2019)
Bidikmisi Tuition Fee Assistance Program is an education fee assistance program for prospective students who are economically disadvantaged and have good academic potential. STMIK PPKIA is one of the universities that also organizes the bidikmisi scholarship program. In the selection process, STMIK PPKIA still uses manual calculations with Microsoft Excel without using methods and applications. For this reason, a system is needed that can help the bidikmisi scholarship selection process at STMIK PPKIA by designing a decision support system to help rank the eligibility of prospective bidikmisi scholarship recipients. This decision support system uses Bayes' Theorem, by taking a sample of bidikmisi applicant data in 2016. In Bayes' Theorem, each probability of being accepted and the probability of not being accepted are calculated which are interrelated. Based on the results of the Analysis using Bayes' Theorem, out of 25 applicants, students who are eligible for the bidikmisi scholarship are 60% = 15 students and the number of students who are not eligible for the bidikmisi scholarship is 40% = 10 students.